2018
DOI: 10.1002/14651858.cd006468.pub6
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation for people with cancer and central venous catheters

Abstract: The evidence was not conclusive for the effect of LMWH on mortality, the effect of VKA on mortality and catheter-related VTE, and the effect of LMWH compared to VKA on mortality and catheter-related VTE. We found moderate-certainty evidence that LMWH reduces catheter-related VTE compared to no LMWH. People with cancer with CVCs considering anticoagulation should balance the possible benefit of reduced thromboembolic complications with the possible harms and burden of anticoagulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 140 publications
0
51
1
1
Order By: Relevance
“…This difference may relate to bias risk but could also be explained by trial characteristics: cancer and treatment duration are risk factors for major bleeding, and three out of five low-risk-of-bias trials included oncological patients who were generally treated for a longer duration [26]. The increased risk of major bleeding in the subgroup of oncological patients was comparable to that reported in previous systematic reviews for this patient category [6,7]. Conversely, the risk of major bleeding for other patient types was low compared to that indicated in other systematic reviews [10,11,25].…”
Section: Considerations On the Optimal Prophylactic Dosementioning
confidence: 50%
See 2 more Smart Citations
“…This difference may relate to bias risk but could also be explained by trial characteristics: cancer and treatment duration are risk factors for major bleeding, and three out of five low-risk-of-bias trials included oncological patients who were generally treated for a longer duration [26]. The increased risk of major bleeding in the subgroup of oncological patients was comparable to that reported in previous systematic reviews for this patient category [6,7]. Conversely, the risk of major bleeding for other patient types was low compared to that indicated in other systematic reviews [10,11,25].…”
Section: Considerations On the Optimal Prophylactic Dosementioning
confidence: 50%
“…Effect estimates were rather similar regardless of bias risk (low risk RCTs estimated an RRR of 35%, while all RCTs combined estimated an RRR of 41%), suggesting we may base our conclusions on the more accurate estimates derived from the meta-analyses of all trials. Previous systematic reviews on thrombosis prophylaxis have found larger relative risk reductions [6,7,10,25]. This could indicate that low-dose LMWH may be slightly less effective for the prevention of VTE than more frequently used higher doses.…”
Section: Considerations On the Optimal Prophylactic Dosementioning
confidence: 93%
See 1 more Smart Citation
“…Prophylactic anticoagulation is not well established because of conflicting data and lower rates of thromboembolism reported in contemporary studies 1 than in previous studies. 2 A Khorana score of 3 or higher has been shown to be a risk factor for such events. 3 In the CASSINI trial, which involved patients with a Khorana score of 2 or higher, 424 of 841 patients had a central venous catheter.…”
Section: Dr Carrier and Colleagues Replymentioning
confidence: 99%
“…Estudo in vitro verificou que a técnica de turbilhonamento permite melhor retirada do material proteico do lúmen do dispositivo quando comparado com a técnica de infundir SF de maneira contínua 6,10,17 . O Locking por sua vez é considerado uma injeção intraluminal, realizado com solução salina ou solução salina com heparina, efetuadas em intervalos de tempo e volume limitado com objetivo de manter o cateter permeável 6,10 . Não existe consenso na literatura em relação à dose adequada para a solução heparinizada, 150 UI/3ml, 500 UI/5ml, 1000 UI/3ml quando comparado ao SF na manutenção da permeabilidade 13,18 . O intervalo para realização Locking para DAVC é de 4 semanas.…”
Section: Cuidados Na Manutenção Da Permeabilidade Dos Davcunclassified